5S rDNA chromosomal mapping and COI sequence analysis reveal differentiation among distinct populations of a characid fish Serrapinnus notomelas - Mariguela, T. C. [UNESP]; Paiva, L. R. S. [UNESP]; Foresti, Fausto [UNESP]; Oliveira, C. [UNESP] (Springer, 2011)
Cheirodontinae comprises a small-sized fish group with a wide geographical distribution throughout Central and South America, mainly in Brazilian Basins. The species Serrapinnus notomelas is widely distributed in the Upper Parana River Basin. In this work, chromosomal mapping of 5S ribosomal RNA (rRNA) gene was performed trough fluorescence in situ hybridization (FISH) in speciemens from three distinct localities belonging to two basins in the São Paulo State. All populations presented 5S clusters in two chromosome pairs. One additional pair was detected in samples from the Rio Paraitinguinha (Tiete Basin), and two additional pairs were detected in the population from Corrego Campo Novo (Tiete Basin). Analyses with partial sequences of COI were performed to verify the interelationship among the studied specimens, revealing Corrego Campo Novo population as a sister-group to the clade formed by the two other populations. The samples from Rio Paraitinguinha and Recanto dos Cambaras presented two distinct haplotypes each, while five haplotypes were observed in the Corrego Campo Novo population, sugesting that this could be older than the other populations. None of the nine haplotypes were shared among the three populations. The similarities and differences observed among the three populations using cytogenetic data and COI analysis are not related to geographic distances that separate the samples, suggesting that the origin of the Rio Paraitinguinha and Recanto dos Cambaras populations may be related to faunal exchanges. Additionally, the present data suggest that the analyzed populations of S. notomelas may be on independent evolutionary trajectories but in a very initial diversification stage. Moreover, the use of integrative information, such as molecular and chromosomal data in the analysis of population divergence and evolutionary trajectories in freshwater fishes is reinforced.
Keywords: Cheirodontinae; Chromosome polymorphism; Cytochrome oxidase I; Fluorescence in situ hybridization; Haplotypes; Mitochondrial gene